2020
DOI: 10.1042/bsr20201094
|View full text |Cite
|
Sign up to set email alerts
|

The coronary artery calcium score is linked to plasma cholesterol synthesis and absorption markers: Brazilian Longitudinal Study of Adult Health

Abstract: Abstract It is controversial whether atherosclerosis is linked to increased intestinal cholesterol absorption or synthesis in humans. The aim of the present study was to relate atherosclerosis to the measurements of plasma markers of cholesterol synthesis (desmosterol, lathosterol) and absorption (campesterol, sitosterol). In healthy male (n=344), non-obese, non-diabetics, belonging to the city of São Paulo branch of the Brazilian Longitudinal Study of Adult Heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
5
1
Order By: Relevance
“…The concentrations of these markers are almost comparable between these studies. In contrast, a report from Brazil 13) reported a much lower Campe concentration in males (1.368±0.960 μg/mL) than that in our results (median value 4.30 μg/mL). As BMI is inversely associated with Campe, as shown in this study, the difference in Campe levels may be explained by the difference in BMI between studies.…”
Section: Association Of Serum Lipid Parameters With Non-contrasting
confidence: 99%
See 1 more Smart Citation
“…The concentrations of these markers are almost comparable between these studies. In contrast, a report from Brazil 13) reported a much lower Campe concentration in males (1.368±0.960 μg/mL) than that in our results (median value 4.30 μg/mL). As BMI is inversely associated with Campe, as shown in this study, the difference in Campe levels may be explained by the difference in BMI between studies.…”
Section: Association Of Serum Lipid Parameters With Non-contrasting
confidence: 99%
“…Serum or plasma levels of these biomarkers in "healthy" populations have been reported and are summarized in Supplemental Table 1 5,9,[12][13][14] . However, criteria for the selection of subjects were different among studies, leading to different study populations and different results.…”
Section: Introductionmentioning
confidence: 99%
“…We did not find associations between cIMT and the synthesis (desmosterol and lathosterol) and absorption (campesterol and sitosterol) cholesterol markers. Similarly, in a population of young Finnish men in their usual diet were not observed associations or correlations between cholesterol synthesis and absorption with a vascular structure measured by cIMT [ 12 ]. Our results corroborate those of Nunes et al showing increased cholesterol synthesis and absorption characterized, respectively, as high concentrations of desmosterol and campesterol when properly corrected for age, BMI, WC, hypertension, TC, smoking, and HOMA-IR representing primary causes of CAD, but not of the common carotid artery atherosclerosis [ 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Like cIMT, the carotid plaque has also been associated with cardiovascular risk, which could be used as a prognostic marker for future cardiovascular events, however, the extent to which the increase in cIMT is related to the future development of the carotid plaque is not entirely clear [ 9 , 10 ]. The relationship between subclinical atherosclerosis determined by cIMT and changes in cholesterol homeostasis was previously explored, but the findings are still controversial [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Synthetic markers and absorption markers of cholesterol are more sensitive to cholesterol metabolism than each marker, which has been pointed out in previous studies on cholesterol synthesis [ 32 ]. Moreover, recent studies have shown that increased cholesterol synthesis and absorption is a major cause of coronary heart disease [ 33 ].…”
Section: Discussionmentioning
confidence: 99%